The Role of Nrf2 in Hearing Loss - Dafei Li; Dafei Li; Haiyan Zhao; Haiyan Zhao; Zhong-Kai Cui; Zhong-Kai Cui; Guangyong Tian; Guangyong Tian (Frontiers Media S.A., 2021)
Hearing loss is a major unresolved problem in the world, which has brought a heavy burden to society, economy, and families. Hair cell damage and loss mediated by oxidative stress are considered to be important causes of hearing loss. The nuclear factor erythroid 2-related factor 2 (Nrf2) is a major regulator of antioxidant capacity and is involved in the occurrence and development of a series of toxic and chronic diseases associated with oxidative stress. In recent years, studies on the correlation between hearing loss and Nrf2 target have continuously broadened our knowledge, and Nrf2 has become a new strategic target for the development and reuse of hearing protection drugs. This review summarized the correlation of Nrf2 in various types of hearing loss, and the role of drugs in hearing protection through Nrf2 from the literature.